THE INVESTIGATION OF THE DEVELOPMENT OF A CREAM COMPOSITION WITH THE SAPROPEL EXTRACT - Strus, Oksana; Polovko, Natalya; Plaskonis, Yuliya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was the development of cream with sapropel extract on the emulsifying base and the investigation of the possibility for cream samples to be in future applied in medicine, cosmetics, and veterinary. Methods: To carry out the research a set of methods (centrifugal, thermal, and potentiometric) to analyze colloidal and thermal stability and determine pH values of the tested samples were used. Organoleptic characteristics of the tested samples and possible signs of physical instability were studied. Rheological properties of the samples were determined on the rotating viscometer. The method of microscopic analysis was carried out to analyze the stability of the emulsion system. Results: The research outcomes revealed that all the prototype samples have thermal and colloid stability, neutral pH value, and consistency that depends on the content of the oil phase and the emulsifying mixture. The samples, containing 15% of Vaseline oil and 4% and 6% of emulsifier no. 1, have low viscosity indexes, and the sample with 10% of emulsifier has a rather dense consistency. The samples containing 20% of oil phase possess unsatisfactory organoleptic properties. Since the sample with 4% of emulsifier possessed low rates of viscosity and phase separation occurred during its storage. Microscopic studies have shown that the sample containing 6% of emulsifier no. 1 exhibits monodisperse and a uniform roundness of drops that indicates the stability of the system. Conclusion: The outcome of the research is the development of the composition of the cream with sapropel extract with the emulsifying base containing 15% of corn oil, 6% of emulsifier no. 1, and 1% of Cetostearyl alcohol and purified water.